Upregulation of the Long Noncoding RNA HULC by Hepatitis C Virus and Its Regulation of Viral Replication. (9th June 2020) - Kitabayashi, Juria; Shirasaki, Takayoshi; Shimakami, Tetsuro; Nishiyama, Tomoaki; Welsch, Christoph; Funaki, Masaya; Murai, Kazuhisa; Sumiyadorj, Ariunaa; Takatori, Hajime; Kitamura, Kazuya; Kawaguchi, Kazunori; Arai, Kuniaki; et al.
Abstract: Background: Many long noncoding RNAs (lncRNAs) have important roles in biological processes. The lncRNA HULC was found to be upregulated in human hepatoma tissues. HULC is thought to be involved in multiple steps of hepatoma development and progression; however, the relationship between HULC and hepatitis C virus (HCV) infection, which is a leading cause of hepatoma, remains unclear. Methods: We examined the effect of HCV replication on HULC expression and the underlying mechanism using cell culture systems. Subsequently, we tested the effect of HULC suppression and overexpression on HCV replication. Finally, we examined the impact of HCV eradication on HULC expression using human liver tissue and blood samples. Results: HCV replication increased HULC expression in cell cultures. A promoter assay showed that an HCV nonstructural protein, NS5A, increased HULC transcription. HULC suppression inhibited HCV replication; conversely, its overexpression enhanced HCV replication. These effects on HCV replication seemed to occur by the modification of HCV translation. Measurements from human liver and blood samples showed that HCV eradication significantly reduced HULC levels in the liver and blood. Conclusions: HCV infection increases HULC expression in vitro and in vivo. HULC modulates HCV replication through an HCV internal ribosome entry site–directed translation step. Abstract : HULC is a long noncoding RNA identified from human liver tissue. We found that HULC was upregulated by hepatitis C virus (HCV) infection in vivo and in vitro and that HULC modulated HCV replication through an HCV translation step.